THE TAWANTINSUYU IN ALLAQMARCA, CARAYBAMBA, AYMARAES PROVINCE, APURIMAC - van Dalen Luna, Pieter (2014)
The state of Tawantinsuyu got to include in its maximum expansion, almost the entire territory of the Andes. To achieve this magnificent expansion had to absorb the different sociopolitical entities occupying the Andes at different latitudes. This situation was made possible by implementing a series of political domination strategies, applied according to the socio cultural reality of each. The territory of the nation Aymaraes (Late Intermediate) was no exception. After the annexation of Aymaraes, new settlements built Tawantinsuyu control and other ancient founded by Aymaraes be reoccupied.